Memories of the Gate: On the Rhetoric in The Pilgrim's Progress and Its Chinese Versions - Chu, Xiaobai (Religions, 2019)
The Pilgrim's Progress was one of the most popular translated novels in China from the late 19th until the 20th century. In this paper, I argue that one of the main reasons for the book's success in China lies in an intricate rhetoric of the original version, which focuses on the memories of the Gate, and in the skillful transformation of this rhetoric into the Chinese versions. By analyzing this rhetoric and its transformation, this paper shows how The Pilgrim's Progress marked the cultural memories of the Gate in China's modern period and provides a theoretical foundation on which studies on contemporary Chinese translations of this book can build.